Blue Carbon Potential of Mangrove Ecosystem on the Coast of Negeri Waai, Central Maluku Regency - Rahman, Rahman; Tuahatu, Juliana W.; Tuhehay, Christin (Jurnal Ilmu Kehutanan, 2024)
The mangrove ecosystem contributes to climate change mitigation by absorbing carbon dioxide gas. The shoreline of Negeri Waai, Central Maluku Regency (CMR), becomes one of Indonesia’s promising mangrove ecosystem habitats for carbon absorption. Therefore, this research aimed to assess the blue carbon potential of mangroves on the coast of Negeri Waai, CMR. This research collected data using the quadrant transect method (10 x 10 m) and placed randomly in 65 quadrants. The analysis of blue carbon potential used an allometric approach to above and below-ground biomass (AGB and BGB). The results showed that the total blue carbon mangrove stock on the coast of Negeri Waai was 73.22 ton C/ha, consisting of 49.44 tons C/ha above-ground carbon (AGC) and 23.78 tons C/ha below-ground carbon (BGC). Sonneratia alba contributed the most extensive carbon stock, namely 70.69 ton C/ha, consisting of 47.53 tons C/ha AGC and 23.16 tons C/ha BGC. This result was relatively low compared to the global average of blue carbon in mangroves, 134 ton C/ha. Based on this result, efforts were needed to restore the mangrove ecosystem, increase the potential for carbon absorption, and mitigate climate change.